1999
DOI: 10.1016/s0009-9236(99)70034-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of clarithromycin on the metabolism of omeprazole in relation to CYP2C19 genotype status in humans*

Abstract: Clarithromycin inhibits the metabolism of omeprazole. Drug interaction between clarithromycin and omeprazole may underlie high eradication rates achieved by triple therapy with omeprazole, amoxicillin, and clarithromycin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
76
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(87 citation statements)
references
References 33 publications
10
76
1
Order By: Relevance
“…It has been confirmed that clarithromycin reduces the elimination of drugs metabolized by CYP3A, such as midazolam (Gorski et al, 1998), omeprazole (Furuta et al, 1999), and cisapride (van Haarst AD et al, 1998;Piquette, 1999) in vivo. Because olopatadine, like imipramine, contains an alkylamino moiety there was a possibility that it also might inhibit P450 activities via the formation of MIC.…”
Section: Fig 2 Mass Spectra Of M1 (A) M3 (B) and Olopatadine (C)mentioning
confidence: 92%
“…It has been confirmed that clarithromycin reduces the elimination of drugs metabolized by CYP3A, such as midazolam (Gorski et al, 1998), omeprazole (Furuta et al, 1999), and cisapride (van Haarst AD et al, 1998;Piquette, 1999) in vivo. Because olopatadine, like imipramine, contains an alkylamino moiety there was a possibility that it also might inhibit P450 activities via the formation of MIC.…”
Section: Fig 2 Mass Spectra Of M1 (A) M3 (B) and Olopatadine (C)mentioning
confidence: 92%
“…1) Recently, Furuta et al 15) empirically reported that an extra-high dose of omeprazole (40 mgϫ3/d) achieved eradication in an extensive metabolizer.…”
Section: 3)mentioning
confidence: 99%
“…11,12) In anti-H. pylori therapy using omeprazole (20 mgϫ2/d for 1 week), amoxicillin (500 mgϫ4/d for 1 week), and clarithromycin (200 mgϫ4/d for 1 week), patients who were poor metabolizers all achieved eradication, while 17% of extensive metabolizers failed. 13,14) Several studies have shown that this therapeutic inefficacy might be overcome by high-dose omeprazole.1) Recently, Furuta et al 15) empirically reported that an extra-high dose of omeprazole (40 mgϫ3/d) achieved eradication in an extensive metabolizer.In the present study, a single oral dose of omeprazole 20, 40, and 80 mg was administered to 7 healthy Japanese subjects with the CYP2C19 genotype. The recommended dose of omeprazole for extensive metabolizers was estimated in anti-H. pylori therapy based on pharmacokinetic considerations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing use of thalidomide raises the possibility of metabolic interactions with other prescription medications. 13) Clinically important interactions between thalidomide and coadministered therapeutics may affect the activation or detoxification of thalidomide and other drugs giving rise to attenuation or amplification of biological effects and/or toxicities. While metabolic studies have been performed in animals, 6) to date there have been only a few human studies.…”
mentioning
confidence: 99%